2011
DOI: 10.1007/s10433-011-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Learning you are “at risk”: seniors’ experiences of nutrition risk screening

Abstract: Nutrition risk screening can help identify community-dwelling older adults who may benefit from nutrition education and interventions to improve food intake. Research has shown, however, that older adults who are found ''at risk'' through nutrition screening commonly do not see themselves at risk, and many do not follow through with accessing recommended nutrition services. Thus, the purpose of this qualitative study was to examine older adults' experiences of learning they were at risk through nutrition scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…Similarly, assessment refusal has been reported in other Australian studies, with the reasons also unclear . However, an investigation of Canadian community living seniors regarding malnutrition risk found that many who were classified at risk did not understand what being at risk meant or did not view themselves at risk . The study's researchers suggested the term ‘at risk’ may be confusing and perceived negatively .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Similarly, assessment refusal has been reported in other Australian studies, with the reasons also unclear . However, an investigation of Canadian community living seniors regarding malnutrition risk found that many who were classified at risk did not understand what being at risk meant or did not view themselves at risk . The study's researchers suggested the term ‘at risk’ may be confusing and perceived negatively .…”
Section: Discussionmentioning
confidence: 76%
“…13,32 However, an investigation of Canadian community living seniors regarding malnutrition risk found that many who were classified at risk did not understand what being at risk meant or did not view themselves at risk. 33 The study's researchers suggested the term 'at risk' may be confusing and perceived negatively. 33 It is not clear how the term 'malnutrition' is perceived by the elderly and further investigation into their perceptions is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, font was made larger and bolding removed in some areas to promote readability and the SCREENII score was removed, as this was not readily interpretable or meaningful to the older adult users. Prior work with older adults, identified that 'risk' terminology was not well understood and could be inflammatory [24]. Thus with the removal of the score, concepts of 'where you are doing well' and 'where you can improve' were used to build the tailored messaging.…”
Section: Development Of Nutri-escreen®mentioning
confidence: 99%
“…As a contrast to all the statistical evidence from survey and demographic data reported in the articles described so far, this issue includes one report from a qualitative study of people's responses to being notified that their pattern of nutrition holds health risks (Reimer et al 2012). The European Journal of Ageing receives an increasing number of submissions based on qualitative studies.…”
mentioning
confidence: 99%